2018
DOI: 10.1038/s41598-018-32870-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of DHH and GLI1 in adrenocortical autograft regeneration in rats

Abstract: Bilateral adrenalectomy forces the patient to undergo glucocorticoid replacement therapy and bear a lifetime risk of adrenal crisis. Adrenal autotransplantation is considered useful to avoid adrenal crisis and glucocorticoid replacement therapy. However, the basic process of regeneration in adrenal autografts is poorly understood. Here, we investigated the essential regeneration factors in rat adrenocortical autografts, with a focus on the factors involved in adrenal development and steroidogenesis, such as Hh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…7) even though the gonad was intact in the adrenocortical autografted rat, unlike the Lhcgr upregulation found in post-gonadectomy-induced adrenal hyperplasia. Our histological analysis showed no obvious adrenal hyperplasia in the autografts 8 .…”
Section: Effect Of Acth On Adrenocortical Regeneration Foetal Adrenomentioning
confidence: 58%
See 3 more Smart Citations
“…7) even though the gonad was intact in the adrenocortical autografted rat, unlike the Lhcgr upregulation found in post-gonadectomy-induced adrenal hyperplasia. Our histological analysis showed no obvious adrenal hyperplasia in the autografts 8 .…”
Section: Effect Of Acth On Adrenocortical Regeneration Foetal Adrenomentioning
confidence: 58%
“…In the search for factors affecting post-transplant adrenocortical autograft remodelling and regeneration, we found that Dhh was upregulated and Shh was downregulated in the regeneration step of rat adrenocortical autograft 8 . The HH signalling pathway may participate in adrenocortical autograft regeneration as well as adrenal cortex development.…”
Section: Gata4/6 Regulate Dhh Transcription In Rat Adrenocortical Autmentioning
confidence: 99%
See 2 more Smart Citations
“…The interactions of the three HH factors are complicated. In the adrenal gland, SHH and DHH act synergistically [114]; In the Dhh -mutant epididymis, SHH plays a compensatory role in order to maintain the stability of the signaling pathway [21].…”
Section: Introductionmentioning
confidence: 99%